Position for the Formulation of the Principle of Ultimum Remedium in the Criminal Law Codes in Various Countries - Adhari, Ade; Pujiyono, Pujiyono; Shidarta, Shidarta; Widyawati, Anis; Suryani, Leony Sondang (Universitas Negeri Semarang, 2024)
This article provides a comprehensive analysis of a fundamental and universal principle in criminal law: the principle of ultimum remedium. This principle advocates for the use of criminal sanctions as a last resort, to be employed only when all other avenues have been exhausted. The primary focus of this study is to examine how the principle of ultimum remedium is articulated within the criminal codes of various countries. The countries selected for this analysis—Germany, Slovenia, Croatia, the Czech Republic, Kosovo, Montenegro, and Kyrgyzstan—were chosen randomly. By scrutinizing these formulations, the study aims to delineate an ideal framework for the application of the ultimum remedium principle. This research utilizes a doctrinal methodology, and through this lens, the article finds that legislators in numerous countries frequently integrate the principle of ultimum remedium implicitly within provisions that address basic principles and limitations of the use of criminal law, basic principles and limitations of criminal law enforcement, basic principles and limitations of criminal sanctions, and basics of criminal accountability. Nonetheless, some countries have explicitly codified the principle of ultimum remedium within provisions titled